Construction logistics in dense urban areas - A qualitative study on the challenges and solutions for construction logistics in dense areas - Shakir, Rebar; Sattar, Farid (My University, 2022)
Population growth is one of the emerging issues of the world, this growth increases the demand for constructing new buildings. Likewise, there is also a significant increased interest in living in urban areas. As a result of these two factors, building in dense urban areas becomes more difficult and complex, thereby affecting construction logistics within the projects. In dense urban areas, construction sites face numerous challenges, such as lack of space, traffic congestion, transportation (off-site issues) among many others. The difficulties regarding construction logistics within dense areas has a large negative impact on the stakeholders involved, but it is also the least managed. Thus, the aim of this thesis is to understand the off-site logistical challenges, and the corresponding solutions for those challenges, and offer future perspectives. In order to achieve the aim of this thesis a qualitative study has been deployed based on semi-structured interviews with managers responsible for logistics. Prior to the empirical work, a literature review conducted to frame the theoretical background of this research. Seven construction projects have been selected to be included in the empirical data. The projects are all located within the dense parts of Gothenburg and are all commercial buildings. The findings indicate that there are commonalities and similarities among the projects, as well as some project-specific challenges. The most common challenges identified during the interviews were a lack of on-site space, consideration of nearby stakeholders, and transportation to the site. According to the interviewees, the most frequently launched solutions to these challenges were the use of a digital planning system (DPS). While the literature advocated for three other solutions to help with the arising challenges, such as construction consolidation centers (CCC), third-party logistics (TPL), and construction logistics plan (CLP). Nonetheless, empirical data show that the selection of logistical solutions is influenced by the logistics managers knowledge and experience, the magnitude of the project, and the location of the project. The respondents were all advocating for increased use of digital tools to improve construction logistics, while no further elaboration was provided, all of the interviewees agreed that additional digital tool implementations are required. Additionally, intangible factors such as increased communication, collaboration, and transfer of gained experience from prior projects were also identified as a means to improve construction logistics.
Keywords: Construction logistics, densification, off-site, construction consolidation centers, third-party logistics, construction logistics plan, digital planning system